Interactions Between the Gut Microbiome and Acute Pancreatitis: Insights into Pathophysiology and Treatment - Miga-Orczykowska, Nadia; Sajkiewicz, Ilona; Lemieszek, Paulina; Jasiuk, Ilona; Wótowicz, Justyna; Pustelniak, Martyna; Krukar, Katarzyna; Łukaszewska, Ewa; Rudnicka, Katarzyna; Kister, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction and purpose Acute pancreatitis (AP) is a prevalent abdominal condition that leads to hospitalizations worldwide. It involves an inflammatory response caused by the premature activation of trypsinogen and other enzymes, leading to the pancreas digesting itself. While most AP cases are mild and resolve on their own, around 15-20% of patients experience severe AP with organ failure, which carries a mortality rate of up to 30%. In recent years, the influence of gut microbiome imbalances on various diseases has gained attention. This study aims to provide an overview of current knowledge on the role of gut microbiota dysbiosis in the development and progression of acute pancreatitis. Material and methods This review is based on information gathered from the PubMed database. We performed a search using the keywords: "acute pancreatitis," "microbiome," and "dysbiosis," with a focus on articles published between 2018 and 2024. Results Research has shown a link between gut dysbiosis and a range of conditions, including digestive, metabolic, and cancer-related disorders. The pancreas has a well-documented connection with the intestines, with its exocrine activity affecting gut microbiome composition. This relationship is commonly known as the "gut–pancreas axis." Conclusion The interplay between the pancreas and gut microbiota is thought to contribute to the pathophysiology of acute pancreatitis. Continued investigation into this connection may pave the way for novel diagnostic and treatment approaches.